2014
DOI: 10.1002/ps.3851
|View full text |Cite
|
Sign up to set email alerts
|

Induced resistance by oxidative shifts in pigeonpea (Cajanus cajan L.) following Helicoverpa armigera (Hübner) herbivory

Abstract: The increase in activities of PPO, DAO, PAO, PAL and TAL and higher proline and lower MDA content upon herbivory suggested their integrated contribution in providing resistance to pigeonpea against H. armigera.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…However, we detected levels of PPO activity in the resistant progenies (52.12 ± 7.14 units) to be more than two-fold higher than the activity in either the tolerant (23.130 ± 2.94 units) or susceptible saplings (24.845 ± 0.194 units), suggesting a role for this enzyme in resistance to P. lata-induced galling. This is consistent with the finding in pigeon pea (Cajanus cajan L.), where genotypes resistant to Helicoverpa armigera infestation were found to have significantly higher PPO activity than in susceptible genotypes (Kaur et al, 2015). Thus, increased levels of PPO can be correlated with increased resistance to P. lata-induced galling in Milicia spp.…”
Section: Discussionsupporting
confidence: 90%
“…However, we detected levels of PPO activity in the resistant progenies (52.12 ± 7.14 units) to be more than two-fold higher than the activity in either the tolerant (23.130 ± 2.94 units) or susceptible saplings (24.845 ± 0.194 units), suggesting a role for this enzyme in resistance to P. lata-induced galling. This is consistent with the finding in pigeon pea (Cajanus cajan L.), where genotypes resistant to Helicoverpa armigera infestation were found to have significantly higher PPO activity than in susceptible genotypes (Kaur et al, 2015). Thus, increased levels of PPO can be correlated with increased resistance to P. lata-induced galling in Milicia spp.…”
Section: Discussionsupporting
confidence: 90%
“…These enzymes control the accumulation of H 2 O 2 and their activity is positively correlated with the intensity and duration of stress in plant cells [57]. Kaur et al [58] found that moderately resistant pigeon pea (Cajanus cajan L.) genotypes exhibited a decrease in MDA content, while moderately susceptible genotypes showed an increase in MDA content in the pod wall following Helicoverpa armigera (Hüb.) feeding.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several studies show that elevated O 3 enhanced the concentration of lignin, a key secondary metabolite determining the palatability of biomass to insects (66). Secondary metabolites play important roles in the defense of plants against herbivores by deterring feeding and reducing digestibility by being toxic at high concentrations (2,(67)(68)(69)(70)(71) but may also attract herbivores at lower concentrations (70,72). Elevated O 3 doses that exceed the toxicological threshold inhibit photosynthesis and thus the biosynthesis of secondary metabolites, whereas low O 3 doses that are below the toxicological threshold stimulate defensive signaling pathways and induce the biosynthesis of secondary metabolites (21,73).…”
Section: Plant-insect Interactions: Is Insect Community Composition A...mentioning
confidence: 99%